Extensor digitorum tendon rupture after anterior ankle arthroscopy : Ruptura tetive ekstenzora digitoruma nakon prednje artroskopije gležnja - Šumanovac, Antun (Array, 2020)
Aim: The aim of this paper is to increase awareness of orthopaedic surgeons about an uncommon yet possible complication of ankle arthroscopy – iatrogenic extensor digitorum rupture. Ankle arthroscopy is becoming more widespread and according to the literature, the complication rate varies from 9% up to 17%. Case report: We are presenting a case of 32-year old police officer who recreationally plays soccer. The patient presented with clear signs of anterior ankle impingement confirmed by X-ray and the MRI. During ankle arthroscopy massive tibial and talar bone spurs were found with significant synovial reaction, nearly 10 loose intraarticular bodies and syndesmotic ossification. The patient was placed in a walking boot and early postoperative recovery went as planned. Physical therapy started 14 days after the procedure. Five weeks after the surgery while dorsiflexing his fingers patient felt a "snap" over his ankle followed by swelling. He couldn't dorsiflex his fingers afterwards. MRI showed a rupture of the common extensor digitorum tendon. The patient was treated with open reconstruction of the tendon and lower leg immobilisation for 6 weeks followed by physical therapy and partial weight bearing. The patient made a full recovery. Conclusion: It is of the utmost importance to keep in mind that ankle arthroscopy alongside it's obvious benefits is not void of complications. Iatrogenic tendon lesion is always possible and should be suspected with any loss of movement in foot and ankle after the procedure. Urgent MRI and immediate reconstruction showed good results in our case.